Sexuální vývoj obézních zen - Danes, L; Sonka, J; Raboch, J (Ceskoslovenska psychiatrie, 1990)
By means of an interview and the questionnaire "Heterosexual Development of Women" [HDW] the authors subjected to sexuological examination 129 obese women aged 20-50 years with a body mass index above 25. As regards the time when overweight developed 29 women developed obesity during the prepubertal period and in 100 of the women obesity developed during adolescence and later. It was revealed that the sexual development of obese women was normal. The mean values in the HDW questionnaire in both subgroups with a different period of development of overweight were all within the normal range.
Keywords: obezita; menstruační cyklus; Female; Adult; dospělí; Obesity; Humans; ženské pohlaví; Menstrual Cycle; Sexual Behavior; lidé; menarche; lidé středního věku; Menarche; Middle Aged; sexuální chování